Strategi Pembelajaran Collaborative Learning dalam Meningkatkan Kemampuan Kerjasama dan Komunikasi dalam Pembelajaran PAI - Faris Anwar; Salsabila Faruza; Gusmaneli Gusmaneli (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
Collaborative learning strategies are approaches that emphasize pressure, cooperation and active involvement between students in a learning community. In Islamic Religious Education learning, implementing this strategy allows students to support each other, share knowledge, and solve problems together, in accordance with the values ​​of mutual assistance contained in Islamic teachings. On the other hand, competitive learning methods place more emphasis on individual efforts to achieve goals, which may not maximize social interaction and collaboration between students. Therefore, the use of collaborative strategies in PAI learning is thought to be more effective in increasing understanding of the material and building students’ cooperation skills and tolerance for other people’s opinions.